2018
DOI: 10.2478/aussoc-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

International Volunteers as Strangers in Szeklerland

Abstract: This paper focuses on volunteer tourism, which is approached as a new phenomenon in a Romanian minority region, i.e. Szeklerland. Volunteer tourism has developed very fast in last decades at international level and mostly in the developed societies. As an alternative tourism form, it is very popular among the youth and gap-year students. Volunteer tourism is a kind of international volunteering which offers opportunity for someone to volunteer and travel at the same time in a foreign country. Volunteer tourism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Millennial activities cannot be separated from engagement with information technology, which can be used to strengthen social integration, active participation, and responsibility. Volunteer tourism by millennials has also become a growing trend in the world with various motivations (Haslebacher et al, 2019;Proyrungroj, 2014;Silló, 2018). A research by Utami et al found that the motivations are to take a vacation, build a relationship, renew a job resume, develop self-ability, and get an adventure.…”
Section: Resultsmentioning
confidence: 99%
“…Millennial activities cannot be separated from engagement with information technology, which can be used to strengthen social integration, active participation, and responsibility. Volunteer tourism by millennials has also become a growing trend in the world with various motivations (Haslebacher et al, 2019;Proyrungroj, 2014;Silló, 2018). A research by Utami et al found that the motivations are to take a vacation, build a relationship, renew a job resume, develop self-ability, and get an adventure.…”
Section: Resultsmentioning
confidence: 99%
“…These characteristics include age, gender (0 = male; 1 = female); ethnicity (1 = Han; 0 = other); household registration (rural, city with prior, and city); parents' marital status (married, separated, divorced, and widowed); parents' highest educational attainment (elementary school or below, middle school, high school, and some college or above); number of family members; and annual family income and welfare status (0 = no; 1 = yes) in the last year. Finally, as previous studies have shown that school environment and local culture make differences in volunteering engagement [32,33], we took college characteristics into account by controlling for specific college influence, or college-fixed effect.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have found that personality traits such as altruistic motivation and empathy were positively related to volunteering [25,29,30]. Individuals with high educational attainment and social capital [1,27,31] and those surrounded by a positive school culture and environment [32,33] also tend to be more involved in volunteering efforts than their counterparts. Finally, intrinsic and extrinsic benefits and rewards, including prestige and training, are positively associated with volunteering [19,28,[34][35][36][37][38].…”
Section: Introduction 1volunteering Among Chinese College Students Du...mentioning
confidence: 99%